Edukasi Literasi Lingkungan untuk Generasi Hijau: Kurangi Sampah Plastik di Kalangan Siswa SMA Negeri 15 Seram Bagian Barat - Handy E P Leimena; Fiyogi D A Tuhumury; Jamal Madi; Ahmad D Patty; Sulthana Ukratalo; Zulfikar Patty; Faris Saman Patty; Muhammar Sukur Rumakur; Kurnain Wenno; M Badru Samallo; Nurul Inayah Patty; Fitria Ukratallo; Mufida Pellu (TOLIS MENGABDI : Jurnal Pengabdian Kepada Masyarakat, 2026)
Plastic waste reduction is one of the critical environmental challenges, particularly for the younger generation, who are the future stewards of the Earth. Therefore, a community service activity was conducted to enhance students’ awareness, knowledge, and behavior regarding responsible plastic waste management. This activity was conducted at SMA Negeri 15 Seram Barat, involving 66 students as participants. The process was divided into three main stages: preparation, implementation, and evaluation. During the preparation stage, planning and development of educational materials on plastic waste management were conducted. The implementation stage included the delivery of materials, discussions, and hands-on practice in environmentally friendly plastic waste management. Meanwhile, the evaluation stage aimed to assess changes in students’ knowledge and attitudes after participating in the activity. The results demonstrated a significant improvement in students’ learning and awareness of the importance of environmental literacy, particularly about reducing plastic waste. The students gained a deeper understanding of the negative impacts of plastic waste on the environment and began to adopt more responsible behaviors in their daily management of plastic waste